The Implementation of Zoom Meeting as Teaching Instrument for Speaking Classes in Profitable English Course - Dewi, Atika Kumala; Anugerahwati, Mirjam (Proceeding International Conference on Education, 2023)
Most people learn English. Science, culture, and international relations necessitate it. Many students join an English course to study with friends outside of school since the course is offline sessions or busy schedules. Therefore, this study investigated using Zoom meetings to teach speaking in several English-learning programs at a prominent English-study institution. Qualitative research was used to gather expert information from entrepreneurs and teachers. This research examines online speaking teaching tactics using observation sheets and Zoom Cloud Meeting interview recordings. The findings showed that teachers' online speaking education methodologies meet students' requirements. They motivate students, utilize real language in relevant circumstances, and engage them. Teacher corrections and comments. Using the natural interaction between speaking and listening may also improve the lesson. Offering students options creates a lively classroom. Each session ends with professors encouraging students to use instructional speaking. This project intends to enhance future English class Internet research.